Primary, secondary metabolites, biochemical and antioxidant activity of Orthosiphon staminues Benth (Misai Kucing) under cadmium exposure - Ibrahim, Mohd Hafiz; Ismail, Ahmad; Omar, Hishamuddin; Mohd Nadzir, Mohd Noor Hisham; Mohd Zain, Nurul Amalina (Sciencedomain International, 2017)
Aims: This study was conducted to evaluate the effects of cadmium (0, 3,6, 9 mg/kg) on the primary, secondary metabolites, biochemical and antioxidant activity in Orthosiphon stamineus. Study Design: Orthosiphon stamineus seedlings were exposed to four levels of Cd (0, 3, 6 and 9 mg/kg) in the form of CdCl2 and were applied to the media during preparation. The experiment was organized in a randomized complete block (RCBD) design with three replications. Each experimental unit consisted of five seedlings, and there was a total of 135 seedlings used in the experiment. Place and Duration of Study: Department of Biology, Faculty of Science Universiti Putra Malaysia between August 2013 to September 2013. Methodology: Total soluble sugar and starch were determined spectrophometically using anthrone reagent, Total phenolics and flavonoid were determined using Folin-Ciocalteu reagent, hydrogen peroxide (H2O2) and lipid peroxidation were measured using potassium iodide (KI) and thiobarbiturate acid (TBA). The antioxidant activity was determined by DPPH reagent. Phenyll alanine lyase activity (PAL) was determined by using transcinnmic acid and cadmium determination by using inductively coupled plasma emission (ICPMS).